Validation of dry land swimming-specific measurement of anaerobic power - Takahashi, S.; Bone, M.; Cappaert, J. M.; Barzdukas, A.; D'Acquisto, L.; Hollander, P.; Troup, J. P. (Biomechanics and Medicine in Swimming. Swimming Science VI, 1992)
The purpose of this study was to develop a simple dryland test that could be used to measure the anaerobic power of competitive swimmers. Sixteen well trained swimmers (17 ± 1 years) completed a series of four submaximal and one maximal effort swims for determination of swimming economy. A lin~ar relationship (V02 vs velocity3 ) was extrapolated to 110% of V02max for each swimmer. Vithin seven days swimmers completed a freestyle swim at this pace for an average of 3.36 ± 0.20 min. During this time, oxygen uptake was measured continuously, accumulated 0 2 uptake was determined at 10 s increments and Oz deficit (anaerobic capacity) calculated (Hermansen and Medb0, 1~84). A blood sample was taken 2 min post-swim for analysis of lactate. A 45 s maximal effort test was also administered using an isokinetic swim bench for determination of total muscular work, average power and force (last 5 s of the bout), and a fatigue ratio (percent decline in power from the first to last 5 s increment). The data revealed significant correlations between the 02 deficit swim and the swim bench test. It is suggested that a 45 s maximal effort test on the swim bench can be used as an accurate way of measuring and predicting a swimmer's anaerobic profile.